2023
DOI: 10.3390/cancers15184426
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Microbiome on Immunotherapy for Gastroesophageal Cancer

Neda Dadgar,
Vinay Edlukudige Keshava,
Moses S. Raj
et al.

Abstract: Immunotherapy has shown promise as a treatment option for gastroesophageal cancer, but its effectiveness is limited in many patients due to the immunosuppressive tumor microenvironment (TME) commonly found in gastrointestinal tumors. This paper explores the impact of the microbiome on the TME and immunotherapy outcomes in gastroesophageal cancer. The microbiome, comprising microorganisms within the gastrointestinal tract, as well as within malignant tissue, plays a crucial role in modulating immune responses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 152 publications
0
1
0
Order By: Relevance
“…The microbiota serves an important role in the mucosa of the gastrointestinal tract [1][2][3]. Several studies have demonstrated that microbes cause DNA damage, promote tumorigenesis, and create a tumor-promoting environment by affecting the immune system [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota serves an important role in the mucosa of the gastrointestinal tract [1][2][3]. Several studies have demonstrated that microbes cause DNA damage, promote tumorigenesis, and create a tumor-promoting environment by affecting the immune system [4,5].…”
Section: Introductionmentioning
confidence: 99%